ETHNO-BOTANICAL CLAIMS COLLECTED FROM TRIBAL AND RURAL PEOPLE OF KADAPA DISTRICT, ANDHRA PRADESH - Ramesh, *C.; Pratap, Goli Penchala; Nagaraju, V.; Sudarsanam, G. (International Journal of Ayurveda and Pharma Research, 2017)
The main aim of the study is to collect the ethnobotanical claims on therapeutic actions of twenty-seven (27) plant species belonging to Fourteen (14) families of angiosperms; practicing by tribal and rural people of Kadapa district, Andhra Pradesh. The study was directed in the tribal villages and provincial regions like; Badvel, Balapalli, Chitvel, Guvvala cheruvu, Kukkaladhoddi, Lankamalai, Mamandur, Palakonda hills, Pulivendula, Rajampeta, Rayachoti and Settipalli in Kadapa District. The governed tribal populations in these regions are Yanadhi accompanied by Yerukula, Nakkala, and Sugalis. Tribal and rural people of the investigated areas have been applying all these plant materials in the form of ash, boiled, crude, curry, decoction etc. for treating 27 disease conditions like; anorexia, bilious affections, piles, burning sensation in the stomach, cold and cough, dandruff, dental diseases, diarrhoea, dyspepsia, redness of eye, facial paralysis, fever, fissures, cracks, flatulence, haemorrhage, hair loss, indigestion, intestinal ulcers, loss of libido, migraine, pains, swellings etc. The botanical name, family name, habit, habitat, part(s) used, flowering and fruiting time, the name of the diseases against which the plants are used and mode of administration with dosage for most of the claims is discussed in detail. The provided information could be used to find new medications of natural origin by the systematic research on pharmacological and clinical trials.